Conversion of l- and d-Phenylalanine to Phenylacetate via Phenylpyruvate in Sorghum Leaf Extracts - Stafford, Helen A. (1979)
The incorporation of dl-[(14)C]phenylalanine into phenylacetate reported previously in leaf enzyme preparations has been found to be catalyzed by two separate enzyme activities leading to phenylpyruvate, one using the l-, the other the d-isomer. Since both reactions occur anaerobically and are increased by the addition of pyridoxal phosphate and α-ketoglutarate, two transaminase (aminotransferase) activities appear to be involved. The activities of the l- and d-dependent forms are approximately equal in a crude particulate fraction, but range from 1:1 to 3:1 in a soluble supernatant fraction. Nonisotopic as well as isotopic assays to separate d- and l-activities are described.